Pengaruh Komite Sekolah Dalam Peningkatan Mutu Sarana Prasarana Pendidikan - Basith, Abdul; Rahmawati, Indriana (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Educational infrastructure is essential in supporting the improvement of the quality of education in schools. This is because the existence of infrastructure facilities facilitate educational activities so that the educational process in schools is not hampered. Provision and maintenance of infrastructure in schools is the responsibility of all school stakeholders including the school committee. Therefore, the purpose of this study is to determine the influence of school committees in improving the quality of educational facilities in SMK 1 Karangan, East Kutai Regency. By using population techniques, there were 15 research subjects and committee members of the Karangan 1 SMKN East Kutai Regency. The research measure is the scale of the role of the school committee in improving educational infrastructure. The results showed that the influence of the school committee was very important in improving the quality of educational infrastructure, it can be shown from the Tstatistic of 11.756 which was greater than Ttable 2.1788, the value of Fstatistic is 138.389 that was greater than Ftable 4.67, and an R-square value of 0.914 or 91.4%. These results showed that the role of the school committee has a major effect on improving the quality of educational infrastructure.